Identification of an osteopontin-like protein in fish associated with mineral formation - Fonseca, V. G. (2014)
Fish has been recently recognized as a suitable vertebrate model and represents a promising alternative to mammals for studying mechanisms of tissue mineralization and unravelling specific questions related to vertebrate bone formation. The recently developed Sparus aurata (gilthead seabream) osteoblast-like cell line VSa16 was used to construct a cDNA subtractive library aimed at the identification of genes associated with fish tissue mineralization. Suppression subtractive hybridization, combined with mirror orientation selection, identified 194 cDNA clones representing 20 different genes up-regulated during the mineralization of the VSa16 extracellular matrix. One of these genes accounted for 69% of the total number of clones obtained and was later identified as theS. aurata osteopontin-like gene. The 2138-bp full-length S. aurata osteopontin-like cDNA was shown to encode a 374 amino-acid protein containing domains and motifs characteristic of osteopontins, such as an integrin receptor-binding RGD motif, a negatively charged domain and numerous post-translational modifications (e.g. phosphorylations and glycosylations). The common origin of mammalian osteopontin and fish osteopontin-like proteins was indicated through an in silico analysis of available sequences showing similar gene and protein structures and was further demonstrated by their specific expression in mineralized tissues and cell cultures. Accordingly, and given its proven association with mineral formation and its characteristic protein domains, we propose that the fish osteopontin-like protein may play a role in hard tissue mineralization, in a manner similar to osteopontin in higher vertebrates.